Relational Pathways to Sociopolitical Control: A Mixed-Methods Study - Kathryn Y. Morgan; Katherine Wiley; Brian D. Christens; Annie B. Clark; Colleen Loomis (Youth, 2025)
Adolescence is a critical period for sociopolitical development, yet research has primarily focused on youth with explicit civic engagement, overlooking the role of community involvement in broader contexts. This mixed-methods study examines how adolescent community involvement—ranging from volunteering and advocacy to participation in sports, religious, and cultural activities—shapes sociopolitical control (SPC) in young adulthood. Using longitudinal quantitative survey data from 352 Canadian families, alongside qualitative interviews with 32 adult participants, we analyze how relationships with parents and peers mediate the link between community involvement and SPC. Regression analyses demonstrate that community involvement in high school predicts SPC at age 25, with parental support and positive peer relationships serving as significant mediators. Mediation analysis further reveals that relationships with mothers exert the strongest indirect effect on SPC, followed by relationships with fathers and peers. Qualitative findings highlight the mechanisms through which relational contexts foster or hinder SPC, illustrating that family values, peer norms, and early exposure to social issues shape long-term civic identity. These results underscore the importance of fostering relationally supportive environments that encourage diverse forms of adolescent community participation, contributing to both individual empowerment and broader democratic engagement.